E-089 Changes in mechanical thrombectomy incidence rate at a comprehensive stroke center before and after Covid-19 shutdown. (23rd July 2022) - Abraham, B; Bohnstedt, B
Abstract : Background: The COVID-19 pandemic has impacted every aspect of our current lives. Therefore, it is important to identify whether there is a change in the number of mechanical thrombectomy (MT) cases that could be attributed to COVID-19 shutdowns. Methods: This is a retrospective cohort study utilizing a prospectively maintained institutional database that tracks MT data at our institution. The study date ranges from August 21, 2018 to October 20, 2021. Patients were dichotomized by the arrival date of March 19, 2020 into pre-and post-COVID-19 shutdown groups. Stroke-onset-to-arrival time is defined as the patient's last known normal to when they arrived at our institution. We utilized univariate analyses to assess MT differences between three settings, 'drip and ship', emergency department, and in-patient admission. Results: Of the 544 patients during this time period, 289 (53.1%) presented during the pre-COVID-19 shutdown timepoint while 255 (46.9%) presented after. Of the 289 pre-COVID-19 patients, 158 (54.7%) arrived by 'drip & ship', 120 (41.5%) presented to the emergency department, and 11 (3.8%) had a stroke in the in-patient setting. Of the 255 post-COVID-19 shutdown patients, 197 (77.3%) arrived by 'drip & ship', 41 (16.1%) presented to the emergency department, and 17 (6.7%) had a stroke in the in-patient setting. The changes in presentation location between the pre-and post-COVID-19 shutdown timepoint were statistically significant (p<0.001). Among the 'drip and ship' patients, the onset-to-arrival time to our institution lengthened from 386.2 to 488.6 minutes after the COVID-19 shutdown (p=0.002) while the onset-to-arrival times did not significantly differ for emergency department and in-patient admits (p>0.05). The arrival-to-puncture time increased from 107.1 minutes to 133.0 minutes after COVID-19 shutdowns for those presenting to the emergency department (p<0.001) while there was no significant difference between 'drip and ship' and in-patient times (p>0.05). The onset-to-recanalization time significantly increased for 'drip and ship' patients from 487.5 to 604.1 minutes after COVID-19 shutdowns (p=0.0037) while the difference was not significant for those presenting to the emergency department. Conclusion: There appears to be a 3-fold decrease in MT presenting to the emergency department at our institution since the COVID-19 shutdown while 'drip and shipped' and in-patient admits have increased slightly. For patients admitted to the emergency department, there was a statistically significant 25-minute increased arrival-to-puncture time after COVID-19 shutdowns. Further monitoring of presentation over the next year as the pandemic wanes will be revealing to any lasting impact on patient triage and treatment based on the COVID-19 pandemic. Disclosures: B. Abraham: None. B. Bohnstedt: 6; C; Proctor/Consultant.